Социологический подход к исследованию легитимности и легитимации - Попова, И. (Социология: теория, методы, маркетинг, 2000)
Legitimation and legitimacy are the notions widely used to characterize the processes taking place in the post-Soviet space. However, to understand all the complexity and depth of legitimacy and its adjacent phenomena one has to go beyond the limits of pure politology and political sociology and enter the sphere of basic sociological notions, such as socialization, personal identification, the system of values, interests and ideological foundations. A sociological investigation of legitimacy and legitimation presumes analyzing a wide range of social, ideological and political contexts of practical activity stipulated by the interests of both population and ruling elite.